Extracorporeal shock wave therapy (ESWT) and radial pressure waves (RPW) May improve post-operative recovery following insertional Achilles tendon surgeries: a case-control pilot study - Amol Saxena; Elizabeth Bondi; Ludger Gerdesmeyer; Adam S. Tenforde (Journal of Orthopaedic Surgery and Research)
Abstract Background Insertional Achilles tendinopathy (IAT) is a common cause of posterior heel pain. While non-surgical management for IAT can result in satisfactory relief, a portion of patients may elect surgical intervention. Post-operative recovery can take on average 7 months to return to physical activity. Identifying treatments to improve post-operative healing is desirable to enhance recovery and return to full physical activity. Materials/Methods All cases from a single surgeon were reviewed from January 2015 to November 2021. Patients (intervention group) were identified who received perioperative extracorporeal focused shockwave (ESWT) and/or radial pressure wave (RPW) therapies and matched by age, sex and surgical technique. The treatment was performed prior to surgery (n = 6), post-operatively (n = 3), or both pre- and post-operatively (n = 3). The primary outcome measure was return to activity (RTA) defined as time from surgery to initiating their athletic activities. The secondary outcome measure was scores on the Roles and Maudsley (RM) obtained at last follow-up visit. Overall group differences were compared using two-sided Student’s T-test for RTA and Fisher exact test for RM, with P-value set at < 0.05. Results We reviewed all cases and identified 12 patients receiving ESWT/RPW who were matched to conventional treatment by age, sex and type of surgery. Seven males and five females were in each cohort, and the average age ± standard deviation of cohort were similar receiving ESWT/RPW and conventional treatment (47.2 ± 11.1 and 48.2 ± 10.6 year-old). Four patients had calcific tendon disease and eight had retrocalcaneal bursitis in each group, and the surgical approach was similar for each condition. The RTA was shorter in those receiving ESWT/RPW (5.5 ± 1.3 compared to 6.8 ± 1.3 months (CI 95%, -2.4 to -0.2, P =.02). The RM trended toward improved values for those receiving ESWT/RPW compared to conventional treatment(P =.07). Conclusions Findings from this study suggest that patients with IAT who underwent perioperative ESWT/RPW therapies may have experienced a faster RTA following surgery.